TOPIC: DIACHRONIC AND SYNCHRONIC APPROACHES TO THE STUDY OF THE VOCABULARY OF THE LANGUAGE - Farokhiddinova Robiyakhon Khushnudbek qizi (TADQIQOTLAR, 2025)
Abstract This article explores two fundamental approaches in linguistic science: the diachronic and synchronic methods of studying vocabulary. The diachronic approach considers the historical development of words and traces changes in meaning, form, and usage over time. In contrast, the synchronic approach focuses on analyzing vocabulary at a specific moment in time, emphasizing structural relationships within the language system. By comparing and contrasting these methods, the article demonstrates that both are essential for a comprehensive understanding of language. Furthermore, the study discusses practical applications of these approaches in fields such as lexicography, language teaching, and corpus linguistics.